A one-pot-one-reactant synthesis of platinum compounds at the nanoscale - Stoppiello, Craig T.; Biskupek, Johannes; Li, Z.Y.; Rance, Graham A.; Botos, Akos; Fogarty, Richard M.; Bourne, Richard A.; Yuan, J.; Lovelock, Kevin; Thompson, P.; Fay, Mike W.; Kaiser, Ute; et al. (Royal Society of Chemistry, 2017)
The preparation of inorganic nanomaterials with a desired structure and specific properties requires the ability to strictly control their size, shape and composition. A series of chemical reactions with platinum compounds carried out within the 1.5 nm wide channel of single-walled carbon nanotubes (SWNTs) have demonstrated the ability of SWNTs to act as both a very effective reaction vessel and a template for the formation of nanocrystals of platinum di-iodide and platinum di-sulphide, materials that are difficult to synthesise in the form of nanoparticles by traditional synthetic methods. The stepwise synthesis inside nanotubes has enabled the formation of Pt compounds to be monitored at each step of the reaction by aberration-corrected high resolution transmission electron microscopy (AC-HRTEM), verifying the atomic structures of the products, and by an innovative combination of fluorescence-detected X-ray absorption spectroscopy (FD-XAS) and Raman spectroscopy, monitoring the oxidation states of the platinum guest-compounds within the nanotube and the vibrational properties of the host-SWNT, respectively. This coupling of complementary spectroscopies reveals that electron transfer between the guest-compound and the host-SWNT can occur in either direction depending on the composition and structure of the guest. A new approach for nanoscale synthesis in nanotubes developed in this study utilises the versatile coordination chemistry of Pt which has enabled the insertion of the required chemical elements (e.g. metal and halogens or chalcogens) into the nanoreactor in the correct proportions for the controlled formation of PtI2 and PtS2 with the correct stoichiometry.